A phase I pharmacodynamic study of GTI-2040, an antisense oligonucleotide against ribonuclotide reductase, in acute leukemias: a California Cancer Consortium study. Issue 10 (2nd October 2016) - Kirschbaum, Mark H.; Frankel, Paul; Synold, Timothy W.; Xie, Zhiliang; Yen, Yun; Popplewell, Leslie; Chen, Robert; Aljitawi, Omar; Tuscano, Joseph M.; Chan, Kenneth K.; Newman, Edward M.
Abstract: We performed a phase I study of GTI-2040, an antisense oligonucleotide against ribonucleotide reductase mRNA, on a novel dosing schedule of days 1–4 and 15–18 by continuous infusion to examine efficacy and tolerability in patients with leukemia. A dose of 11 mg/kg/d was safely reached. Dose-limiting toxicities (DLTs) at the higher levels included elevated troponin I and liver function enzymes. There were no objective responses to GTI-2040 in this study; 7/24 patients were able to complete the predetermined three infusion cycles. Pharmacokinetic and pharmacodynamic studies were performed, indicating a trend towards increasing intracellular drug levels and decreasing RRM2 gene expression with increasing doses. This dose schedule may be considered if appropriate combinations are identified in preclinical studies.